Probiotic Beverage From Pineapple Juice Fermented With Lactobacillus and Bifidobacterium Strains - Nguyen, Bao Toan; Bujna, Erika; Fekete, Noemi; Tran, Anh T. M.; Rezessy-Szabo, Judit M.; Prasad, Ram; Nguyen, Quang D. (Frontiers in Nutrition, 2019)
Pineapple is economically significant plant and the third most important fruit crop in the tropical and subtropical regions of the world. In this study, fermentation of pineapple juice with probiotic bacteria Lactobacillus and Bifidobacterium strains as well as changes of some properties of beverage during storage were investigated. All tested strains exhibited good growth properties on pineapple juice without supplementation of any nutrient compounds. After 24 hours fermentation, the cell counts of lactobacilli passed the level of 5*109 cfu/ml, while the cell number of bifidobacteria reached level of 109 cfu/ml. The highest volumetric productivity (3.5*108 cfu/ml*h) was observed with L. plantarum 299V without addition of prebiotic saccharide. The ratios of lactic acids to acetic acids in the cases of L. plantarum 299V and L. acidophilus La5 were 5.37 and 9.91, respectively. In the case of B. lactis Bb-12, concentration of lactic acid and acetic acid were 6 mM and 23 mM in natural juices, and 15 mM and 21 mM in the case of supplement of prebiotic at 16th hour fermentation, respectively. When supplementation with prebiotic at initiation of fermentation resulted 7 mM lactic acid and 23 mM acetic acid at the end of fermentation with B. lactis Bb-12 strain. Fructose was most preferred sugar for both lactobacilli and bifidobacteria. Both total phenolic content and antioxidant capacity increased slightly during fermentation and dropped during storage period. The microbial population did not change significantly during the first month of storage. After storage period (2 months), the probiotic bacteria lost about 0.11 log cfu/ml viability after treatment with 0.3 % pepsin for 135 minutes, and further 0.1 log cfu/ml after treatment with 0.6 % bile salts, respectively. These values were 10 times higher than data from the fresh fermented pineapple juice. Our results are very promising and may serve good base for development of probiotic pineapple juice.